Assessment of Educational Status of Periodontics and Oral Health and Community Dentistry Departments in Yazd Dental School Using CIPP Model in 2018 - Fahimeh Rashidi Maybodi (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: Considering the changes, which implemented in the dental education program in recent years and also the importance of reviewing their feedback in educational affairs, the purpose of this study was to evaluate the periodontics and dental public health departments of Dental School based on the CIPP evaluation model in 2018. Methods: The present study was performed in a descriptive cross-sectional format on the target population of dental students of 10-12 semesters and professors of the mentioned groups. Context, input, process and product were assessed using a questionnaire consistent with the CIPP pattern checklist. Data were analyzed by ANOVA and T-test via SPSS 16 software. Results: The average scores of professors and students in different areas of the Periodontology Department were as followed: the context (75, 58.6); input (18.9, 1.37); process (68.7, 8.37) and product (56.2, 1.37) fields, respectively. In the Dental Public Health Department, the average scores also included context (50, 3.64); input (25, 5.63); process (100, 58) and product (75, 3.58) areas, respectively.